Short-term, serum-free, static culture of cord blood-derived CD34+ cells: effects of FLT3-L and MIP-1alpha on in vitro expansion of hematopoietic progenitor cells - G Capmany; S Querol; JA Cancelas; J Garcia (Haematologica, 1999)
BACKGROUND AND OBJECTIVE: The use of ex vivo expanded cells has been suggested as a possible means to accelerate the speed of engraftment in cord blood (CB) transplantation. The aim of this study was to fix the optimal condition for the generation of committed progenitors without affecting the stem cell compartment. DESIGN AND METHODS: Analysis of the effects of FLT3-L and MIP-1alpha when combined with SCF, IL-3 and IL-6, in short-term (6 days), serum-free expansion cultures of CB-selected CD34+ cells. RESULTS: An important expansion was obtained that ranged between 8-15 times for CFU-GM, 21-51 times for the BFU-E/CFU-Mix population and 11 to 30 times for CD34+ cells assessed by flow cytometry. From the combinations tested, those in which FLT3-L was present had a significant increase in the expansion of committed progenitors, while the presence of MIP-1alpha had a detrimental effect on the generation of more differentiated cells. However, stem cell candidates assessed by week 5 CAFC assay could be maintained in culture when both MIP-1a and FLT3-L were present (up to 91% recovery). This culture system was also able to expand megakaryocytic precursors as determined by the co-expression of CD34 and CD61 antigens (45-70 times), in spite of the use of cytokines non-specific for the megakaryocytic lineage. INTERPRETATION AND CONCLUSIONS: The results obtained point to the combination of SCF, IL-3, IL-6, FLT3-L and MIP-1alpha as the best suited for a pre-clinical short-term serum-free static ex vivo expansion protocol of CB CD34+ cells, since it can generate large numbers of committed progenitor cells as well as maintaining week 5 CAFC.